Simulation of heterogeneous reaction systems - Behrendt, Frank; Deutschmann, Olaf; Ruf, Bernhard; Schmidt, Rainer; Warnatz, Jürgen (Gas phase chemical reaction systems, 1996)
Bodenstein was the first in the field of catalysis identifying correctly the concentrations of the adsorbed species as controlling element for many heterogeneous reaction systems. While failing to be correct in all details, Bodenstein prepared the ground for many others on their way to a detailed understanding of heterogeneous catalysis kinetics.